2022
DOI: 10.3390/nu14040828
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass and Emotional Eating: Emotional Eater Questionnaire (EEQ) in the Polish Adolescents’ COVID-19 Experience (PLACE-19) Study

Abstract: Stress caused by the Coronavirus Disease 2019 (COVID-19) pandemic may lead to emotional eating which may have a negative impact on the weight status. This study aimed to analyze the association between emotional eating and body mass, as well as changes in body mass during the COVID-19 pandemic, within the Polish Adolescents’ COVID-19 Experience (PLACE-19) Study. A total of 1126 Polish adolescents, aged 15–20, were included. A random quota sampling was performed within a national sample, and emotional eating wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…In a qualitative study, females identified stress as the primary trigger for emotional eating [ 38 ]. During the COVID-19 pandemic, several authors have linked psychological distress to emotional eating, both in adolescents [ 39 ] and adults [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study, females identified stress as the primary trigger for emotional eating [ 38 ]. During the COVID-19 pandemic, several authors have linked psychological distress to emotional eating, both in adolescents [ 39 ] and adults [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that body mass can also be linked with food choice determinants [ 33 ] and dietary patterns [ 34 ]. Similarly, body mass is associated with emotional eating behavior, which is defined as the tendency to eat energy-dense products in response to negative emotions [ 35 ]. Moreover, body mass may be specifically associated with food choices, including the choices of restaurant dishes.…”
Section: Discussionmentioning
confidence: 99%
“…The Emotional Eater Questionnaire was developed by Garaulet [ 14 ] and includes 10 items. It was validated in several other countries [ 15 , 16 , 17 , 18 ] and used as an assessment tool in several projects focused on eating disturbances [ 17 , 19 , 20 , 21 , 22 , 23 , 24 ]. This questionnaire answered the need for an instrument to be used both in research and clinical practice well, and is compliant, easily understood by patients, and interpreted by investigators using the interpretation scale developed by Garaulet.…”
Section: Methodsmentioning
confidence: 99%